2022
DOI: 10.33448/rsd-v11i15.36959
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation technique on the rehabilitation of contaminated areas and the application of Zantedeschia aethiopica (L.) in this process: a narrative review

Abstract: Phytoremediation is an innovative, efficient and eco-friendly technique for the treatment of contaminated areas. This method consists in the use of plant species for extraction, degradation, containment or immobilization of pollutants/xenobiotics. Recently, ornamental plants have been gaining spotlight in remediation studies, precisely because of their aesthetic value and their ability to develop in environments contaminated with heavy metals, textile dyes and pesticides. An important ornamental species for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…In Brazil, the phytoremediation technique has gained interest and obtained important advances in the field of research. Some studies have applied the technique to treat soils contaminated with herbicides and have observed that various types of plants can be used for this purpose, such as ornamental specimens, macrophytes, woody trees, agricultural crops, and grasses (Bergamo, Daquila, and Conte, 2022).…”
Section: Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the phytoremediation technique has gained interest and obtained important advances in the field of research. Some studies have applied the technique to treat soils contaminated with herbicides and have observed that various types of plants can be used for this purpose, such as ornamental specimens, macrophytes, woody trees, agricultural crops, and grasses (Bergamo, Daquila, and Conte, 2022).…”
Section: Metalsmentioning
confidence: 99%
“…In Brazil, studies have been conducted to treat soils contaminated with herbicides through phytoremediation (Galon et al, 2017, Ferreira et al, 2021, Vasconcelo et al, 2020. In these, it was found that there is a diversity of plants capable of acting in this process, among them ornamental specimens, macrophytes, woody trees, agricultural crops, and grasses (Kaushal et al, 2021 apud Bergamo, Daquila, andConte, 2022). Contribuciones a Las Ciencias Sociales, São José dos Pinhais, v.16, n.7, p. 7206-7218, 2023 The phytoremediation technique can be applied in accidents such as the one that occurred in Brumadinho, Minas Gerais, after the rupture of the dam of the Feijão stream mine and others such as Fundão, in Mariana, which occurred in Brazil, since some plant species have the capacity of hyperaccumulation.…”
Section: Introductionmentioning
confidence: 99%